INCREASING DOSES OF GERMANIUM IN THE SOIL ALTER THE PRIMARY METABOLISM OF RADISH PLANTS - Martins Corrêa, Gabriela; Fernandes Rodrigues, Natália; Huther, Cristina Moll; Roberto de Lucena Tavares, Silvio; Ramos de Oliveira, Julia; Neves Verde, Felipe; Pereira da Silva, Josiane (REVISTA DE AGRICULTURA, 2024)
Germanium (Ge) is a chemical element used in several industrial processes. According to the Survey of Rocks and Soils of the Geological Service of Brazil (SGB-CPRM) this element is found in a wide territorial range in the country. Thus, The objective of this study was to evaluate the primary metabolism of Raphanus sativus when grown with different doses of germanium, in relation to photosynthetic performance and growth for three crop cycles. The experiment consisted of growing radish in 7 treatments containing germanium in the soil at concentrations of 0; 0.5; 1; 1.5; 2; 2.5; 3 mg kg-1. Analyses were performed over three complete cycles of the crop, from seedling production, transplanting and harvesting. The parameters analyzed in each cycle were: growth, chlorophyll concentration, chlorophyll a fluorescence, and stomatal conductance. The treatments with concentrations up to 1.5 mg kg-1, in all cycles, presented a better performance. Indicating a possible toxicity for levels above this.